Soil physical quality in integrated crop-livestock-forest systems - Valani, Gustavo Pereira (2024)
Integrated crop-livestock-forest systems aim to sustainably combine cropping, livestock production and forestry systems, contributing to soil quality and ecosystem services. This thesis was divided into six chapters. Chapter 1 systematically reviewed studies about integrated crop-livestock-forest systems and soil quality, bringing the state of the art in this topic and pointing out gaps in the literature. Chapters 2 to 5 studied soil physical quality in six soil management systems, from continuous grazing to partial and fully integrated crop-livestock-forest systems, as well as a native vegetation area, all part of an experiment in Embrapa Southeast Livestock. Chapter 2 assessed physical indicators of soil quality in the topsoil only, Chapter 3 analytically assessed indicators down to 100 cm, Chapter 4 assessed soil porosity by 3D X-ray computed tomography, and Chapter 5 assessed soil structure from visual and analytical methods, as well as their correlation between results from Chapters 2 to 5. Chapter 6 studied the condition of the soil resource and the provision of soil-based ecosystem services in the same above-mentioned grazing systems. The literature review pointed out the lack of studies comparing different integrated systems, the lack of works on integrated systems with trees, and the lack of information of soil quality deeper than 40 cm in the soil, which were all further addressed in this thesis. Findings from Chapters 2 to 5 suggest a degree of soil compaction in all grazing systems down to about 40 cm. Soil physical quality in integrated grazing systems was generally similar to non-integrated systems, despite integrated systems having a higher stocking rate and a heavier load from machinery traffic, which was likely counterbalanced by their more diverse root system. Strong correlations were found between visual, analytical and digital indicators of soil quality, including different methods for assessing soil porosity. Chapter 6 found that the most integrated grazing system accounted for the highest overall soil-based provision of food and fiber. Additionally, carbon sequestration in integrated systems with trees offset enteric methane emissions, which contributes to tackle climate change. Finally, it is recommended that integrated systems use controlled traffic and a diverse crop rotation, including cover crops, to better sustain soil physical quality.